THE SOCIOLOGICAL EXPLANATION OF INDONESIAN MUSLIM FAMILY: Continuity and Change (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
The study indicates that there is a tendency for family characteristics, functions, and structures to be questioned. Many people, for example, would consider unmarried couples, single mothers or single fathers, and homosexual couples to be the same legitimate expressions of family units. However, Indonesian Muslim family takes a more conservative stance, arguing that the family is a divinely inspired institution, with marriage as the starting point of its differentiation. The article explores what the family means for Muslims in general: its normative philosophy, its implementtation in general and the challenges that will be faced. The goal is to offer an introduction to keywords and a general map of the problem. Some cases are presented as explanatory tools. The used method is library research by utilizing the results of previous research and then carried out contextualization in the Indonesian situation. There are several findings and one of the most important one is that within Indonesian muslim context, there are still several values upheld quite conventionally. Even the very basic of family issues that is the definition remains quite conservative and this is legally stated in several policies including the 1974 marriage law. In addition, there are also several interesting changes occur within Indonesian sociology of family and among the issues are roles divisions, divorces and arranged marriages.